2002
DOI: 10.1021/jp0263525
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fluorescent Phospholipid Liposomes Entrapped in Sol−Gel Derived Silica

Abstract: Bilayer lipid membranes (BLMs) have been widely examined as sensing elements for a variety of analytes, in both the vapor and solution phases, using electrochemical, acoustic wave, and fluorescence methods. For successful development of stable sensing devices, it is necessary to be able to immobilize the BLMs in a manner that allows long-term retention of the membrane structure and still permits large-scale structural reorganizations such as phase transitions. In this work, small unilamellar liposomes were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 68 publications
(92 reference statements)
1
48
1
Order By: Relevance
“…21 This is analogous to effects observed in work with thermal unfolding of proteins in silica gel, where a higher free energy (thus higher unfolding temperature) was imposed upon entrapped, folded proteins due to decreased volume available for the unfolded form. 40,41 Since the lipid tails become less dense when undergoing a gel phase to liquid crystalline transition, 42 it is reasonable to believe that the excluded volume effect can be involved.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…21 This is analogous to effects observed in work with thermal unfolding of proteins in silica gel, where a higher free energy (thus higher unfolding temperature) was imposed upon entrapped, folded proteins due to decreased volume available for the unfolded form. 40,41 Since the lipid tails become less dense when undergoing a gel phase to liquid crystalline transition, 42 it is reasonable to believe that the excluded volume effect can be involved.…”
Section: Discussionmentioning
confidence: 56%
“…21 Their work demonstrated that the use of DGS- and SS-derived gels permitted the DPPC liposomes to exhibit phase transitions as they would in solution, while the use of TEOS-derived gels did not. Also, they depicted, via confocal fluorescence imaging, that the liposomes are capable of undergoing a variety of conformational changes once trapped inside of the gel, forming aggregates or bicelles.…”
Section: Introductionmentioning
confidence: 99%
“…Other metal oxides, such as alumina Al 2 O 3 [32] or vanadium oxide V 2 O 5 [33] were also shown to be suitable for biological macromolecules encapsulation. The process was extended to antibodies [34], nucleic acid [35], phospholipids [36], and poly-saccharides [37]. Additionally, several biophysical studies were devoted to the understanding of the behaviour of entrapped species [38,39].…”
Section: Biological Macromolecules Encapsulationmentioning
confidence: 99%
“…A detailed characterization of the physical properties and stability of the immobilized lipid systems was carried out later by the Brennan group. 13 They incorporated liposomes composed of dipalmitoyl phosphatidylcholine (DPPC) in a TEOS sol-gel matrix and observed that the lipid bilayer did not exhibit phase transition suggesting that encapsulation resulted in rupture of these structures. This behavior was attributed to interactions between the lipid and the ethanol resulting as a byproduct of the chemical reactions involved in the formation process of the silica matrix.…”
Section: Introductionmentioning
confidence: 99%